Estimating Global Prevalence of Metabolic Dysfunction-Associated Fatty Liver Disease in Overweight or Obese Children and Adolescents: Systematic Review and Meta-Analysis - Jiaye Liu; Jiaye Liu; Chunyang Mu; Kewei Li; Han Luo; Han Luo; Yong Liu; Zhihui Li; Zhihui Li (Frontiers Media S.A., 2021)
Objectives: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a new terminology updated from non-alcoholic fatty liver disease (NAFLD). We aim to estimate the global prevalence of MAFLD in overweight or obese children and adolescents, by repurposing existing data on fatty liver disease.Methods: We screened relevant articles published up to December 2020. Pooled prevalence was calculated using Logit transformations.Results: Our search returned 35,441 records, of which 156 studies fulfilled the inclusion criteria. The overall prevalence of MAFLD was 33.78% in the general population and 44.94% in a special population based on child obesity clinics, regardless of the diagnostic techniques. For subgroup analysis, MAFLD prevalence was significantly higher in boys compared to girls (36.05 vs. 26.84% in the general population; 50.20 vs. 35.34% in the child obesity clinics-based population). Interestingly, based on study source, the pooled prevalence of MAFLD was 1.5-fold higher in other "fatty liver disease" studies compared to the classical "NAFLD" studies in the general population.Conclusion: MAFLD is highly prevalent in overweight or obese children and adolescents. Raising awareness and urgent actions are warranted to control the MAFLD pandemic across the globe.